2016
DOI: 10.1111/nph.14363
|View full text |Cite
|
Sign up to set email alerts
|

Biological limits on nitrogen use for plant photosynthesis: a quantitative revision comparing cultivated and wild species

Abstract: The relationship between leaf photosynthesis and nitrogen is a critical production function for ecosystem functioning. Cultivated species have been studied in terms of this relationship, focusing on improving nitrogen (N) use, while wild species have been studied to evaluate leaf evolutionary patterns. A comprehensive comparison of cultivated vs wild species for this relevant function is currently lacking. We hypothesize that cultivated species show increased carbon assimilation per unit leaf N area compared w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 66 publications
4
28
0
5
Order By: Relevance
“…Due to higher CO 2 concentrations around Rubisco C 4 plants have much lower rates of oxygenation; this allows them to compromise their Rubisco’s S c/o for a higher kcatc. Thus, their nitrogen investment in Rubisco (and other enzymes in the photorespiratory pathway) is much lower than that of C 3 plants, increasing their PNUE (Rotundo and Cipriotti, ). It has been shown that an efficient use of nitrogen in C 4 photosynthesis lessens nitrogen cost constraints on molecular sequence evolution (Kelly, ).…”
Section: Costs Versus Benefits Of Photorespirationmentioning
confidence: 99%
“…Due to higher CO 2 concentrations around Rubisco C 4 plants have much lower rates of oxygenation; this allows them to compromise their Rubisco’s S c/o for a higher kcatc. Thus, their nitrogen investment in Rubisco (and other enzymes in the photorespiratory pathway) is much lower than that of C 3 plants, increasing their PNUE (Rotundo and Cipriotti, ). It has been shown that an efficient use of nitrogen in C 4 photosynthesis lessens nitrogen cost constraints on molecular sequence evolution (Kelly, ).…”
Section: Costs Versus Benefits Of Photorespirationmentioning
confidence: 99%
“…A recent trait study compared wild and cultivated species for photosynthesis and leaf N [53] and concluded that cultivated species have not yet surpassed the biological limit on N use (for photosynthesis) established by wild species. In physiological terms, WUE can be defined as the ratio of the net rate of carbon fixation (A), to the stomatal conductance to water vapor (g s ; a function of stomatal aperture and density [54]).…”
Section: Water Use Efficiency Of Grain Legume Versus Non-legume Cropsmentioning
confidence: 99%
“…Using an approach similar to those used in other meta-analyses (e.g., [53]), we synthesized leaf trait data for annual grain legume and non-legume crops using meta-analysis of the existing literature . We used a parsimonious approach, only accepting data that met key criteria (Box 1).…”
Section: Water Use Efficiency Of Grain Legume Versus Non-legume Cropsmentioning
confidence: 99%
“…Photosynthetic nitrogen use efficiency (PNUE) is the amount of carbon that can be fixed per unit of nitrogen invested by the plant. Multiple disparate anatomical, physiological and molecular factors contribute to variation in PNUE such that there is a large variation between different plant species 7 .…”
Section: Introductionmentioning
confidence: 99%